Attribute based comparison of cooling techniques and CFD simulation of spray - Singh, Anam (My University, 2015)
High heat transfer techniques are requirement of today’s electronic industry and in this research four high heat transfer techniques spray cooling, jet impinging cooling, two phase microchannel flow cooling technique and single phase microchannel flow cooling techniques are compared on the basis of attributes. In this way the collective approach using multiple attributes are taken to compare the four techniques. To compare the cooling techniques first the different attributes on which the selection of cooling technique depends are collected, then they classified into two broad categories: General Attributes and Specific attributes. Each category is further divided into groups and then subgroups. The codification scheme is also given to codify the attributes. The techniques are compared using MADM-CCSD approach by which16 different experimental results (4 experiments related to each cooling technique) are used to compare the cooling techniques and Jet impinging technique is best among all four techniques. In next section the CFD simulation of spray has been done using DPM (Discrete phase modeling) in ANSYS Fluent commercial software. In this way the simulation is first optimized to use less computer resources without affecting the results. Variation of spray angle, number of nozzles and distance between multiple number of nozzles have been studied on wall film mass, wall film height, uniformity index of wall film and velocity of wall film.
ME, MED
Keywords: Spray; CFD; Boundary Film Formation; Nozzle Angle; Multiple Nozzles; ANSYS; Distance between Nozzles; MADM; CCSD; TOPSIS; Comparision of cooling techniques; MED